Smoking too few cigarettes to be at risk? Smokers' perceptions of risk and risk denial, a French survey. Issue 5 (26th September 2007) - Peretti-Watel, Patrick; Constance, Jean; Guilbert, Philippe; Gautier, Arnaud; Beck, François; Moatti, Jean-Paul
Abstract : Background: Past studies on smokers' risk perception have produced mixed results. We endorsed a new approach to assess smokers' perceptions of risk by asking them to estimate threshold values for the cancer risk associated with daily consumption of tobacco and number of smoking years. We expected that many smokers would endorse a "risk denial" attitude, with threshold estimates higher than their own smoking consumption and duration. Methodology: A French national telephone survey (n = 3820; 979 current smokers) included several questions about smoking behaviours and related beliefs. Results: Among current smokers, 44% considered that smoking can cause cancer only for a daily consumption higher than their own consumption, and an additional 20% considered that the cancer risk becomes high only for a smoking duration higher than their own. Most smokers also agreed with other "risk denial" statements ("smoking is not more dangerous than air pollution, " "some people smoke their whole life but never get sick"). Those who considered they smoked too few cigarettes to be at risk were less likely to report personal fear of smoking related cancer. Conclusion: Risk denial is quite widespread among smokers and does not simply reflect a lack of information about health risks related to tobacco. Fully informing smokers about their risks may necessitate changing the way they process information to produce beliefs and limiting their capacity to generate self exempting beliefs.